Bilingual word-embedding for korean and english without word alignments - Kim, Min Su; Cha, Moon Su; Sohn, Kyung Ah (Lecture Notes in Electrical Engineering, 2018)
In spite of lots of cross-lingual word embedding models for various languages, approaches that support cross-lingual word embedding between languages that have different word order and different origin word are lacking. In this study, we address the problem of cross-lingual word embedding between Korean and English that have different word order and origin and perform experiments to examine its performance behavior. Cross-lingual models have different levels of supervision. For training between languages which have different word order, it is essential to reduce preprocessing time. Therefore, two sentence-level alignment cross-lingual models are chosen for our experiments. Our results show that cross-lingual embedding for Korean and English without word-alignment is possible. We also analyze which bilingual tasks are proper for each trained result by comparing characteristic of each model’s trained result.
Keywords: Bilingual tasks; Cross-lingual; Different origins; Preprocessing time; Sentence level; Word alignment; Word orders